Efficient Nonfullerene Polymer Solar Cells Enabled by a Novel Wide Bandgap Small Molecular Acceptor. Issue 18 (3rd March 2017) - Zhang, Guangjun; Yang, Guofang; Yan, He; Kim, Joo‐Hyun; Ade, Harald; Wu, Wenlin; Xu, Xiaopeng; Duan, Yuwei; Peng, Qiang
Abstract : A wide bandgap small molecular acceptor, SFBRCN, containing a 3D spirobifluorene core flaked with a 2, 1, 3‐benzothiadiazole (BT) and end‐capped with highly electron‐deficient (3‐ethylhexyl‐4‐oxothiazolidine‐2‐yl)dimalononitrile (RCN) units, has been successfully synthesized as a small molecular acceptor (SMA) for nonfullerene polymer solar cells (PSCs). This SMA exhibits a relatively wide optical bandgap of 2.03 eV, which provides a complementary absorption to commonly used low bandgap donor polymers, such as PTB7‐Th. The strong electron‐deficient BT and RCN units afford SFBRCN with a low‐lying LUMO (lowest unoccupied molecular orbital) level, while the 3D structured spirobifluorene core can effectively suppress the self‐aggregation tendency of the SMA, thus yielding a polymer:SMA blend with reasonably small domain size. As the results of such molecular design, SFBRCN enables nonfullerene PSCs with a high efficiency of 10.26%, which is the highest performance reported to date for a large bandgap nonfullerene SMA. Abstract : A wide bandgap small molecular acceptor, SFBRCN, containing a 3D spirobifluorene core flanked with two 2, 1, 3‐benzothiadiazole groups and end‐capped with two highly electron‐deficient (3‐ethylhexyl‐4‐oxothiazolidine‐2‐yl)dimalononitrile units, has been successfully synthesized as a small molecular acceptor for nonfullerene polymer solar cells with a high efficiency of 10.26%.